2019
DOI: 10.1097/md.0000000000015824
|View full text |Cite
|
Sign up to set email alerts
|

Gluteal, abdominal, and thoracic multiple impalement injuries

Abstract: Rationale: Historically, traumatic injuries include penetrating and blunt lesions. Impalement injury represents one of the rarest and potentially dramatic forms of penetrating trauma. If patient reaches hospital alive and is hemodynamically stable, there is a good chance that patient overcomes the traumatic event. However, non-removal of foreign body represents the cornerstone in initial treatment of this type of patients. Patient concerns: A stable 55-year-old woman wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Perineal impalement represents an extremely uncommon type of trauma, being, in the vast majority of cases, associated with severe injuries that can compromise vital structures in the pelvis, abdomen, and even the thorax [ 4 ]. The high morbidity and mortality, highlighted by approximately 25 % of patients who do not survive until hospital admission, underscore the severity of this type of injury, particularly in extensive impalements [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perineal impalement represents an extremely uncommon type of trauma, being, in the vast majority of cases, associated with severe injuries that can compromise vital structures in the pelvis, abdomen, and even the thorax [ 4 ]. The high morbidity and mortality, highlighted by approximately 25 % of patients who do not survive until hospital admission, underscore the severity of this type of injury, particularly in extensive impalements [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thoracoabdominal impalement describes a traumatic lesion due to the abnormal presence of penetrating, long and solid objects involving the thoracic, and the abdominal cavity with diaphragmatic involvement (1). Author describes classically impalements caused by falls, blasts, impalement after an accident in construction areas, in a traffic accident, and impalement following sexual malpractice (2)(3)(4)(5). Depending on its localization, the lesion may involve vital organs such as the heart, lung, liver, kidney, or thoracic vessels; however, most of the time; vital structures are displaced rather than transfixed.…”
Section: Discussionmentioning
confidence: 99%
“…This is an open article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licences/bync/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited recommended by authors (4,7). Depending on the lesion complexity, perioperative care may involve complex management strategies including patient positioning, blood management strategies, and challenging anesthetic management for the surgical procedures.…”
Section: Ann Afr Med Vol 16 N° 2 Mars 2023mentioning
confidence: 99%
See 1 more Smart Citation
“…The first-hand medical handling of the patients who Abdominal CT scan + enhancement + post-processing (image reconstruction) showed that metal penetrating injury of left perineum, pelvis, left sacrum and ilium, the left internal iliac artery distal segment was not clearly displayed due to the artifact, and the relationship with the foreign matter was difficult to assess. suffered from penetrating injuries and the operation process during transportation may be accompanied by some wrong operations or rescue measures, which may aggravate the physical condition and lead to fatal and irreversible damage to these patients (10,11). Nevertheless, the penetrating abdominal injury is part of the trunk injury, it may caused progressive dyspnea, and are in critical condition and hemodynamically unstable.…”
Section: Discussionmentioning
confidence: 99%